2021
DOI: 10.5603/ep.a2021.0060
|View full text |Cite
|
Sign up to set email alerts
|

Determination of neuron-specific enolase in patients with midgut-type tumour treated with somatostatin analogues

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Endokrynologia Polska" are listed in PubMed. The final version may contain major or minor changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
3
4
1
Order By: Relevance
“…On the other hand, in our study, the analysis of concentrations in patients with small intestine lesions did not show a correlation between the degree of malignancy and the values of the marker determined. The results of our study did not confirm literature reports in which the authors indicate statistical differences already between low and intermediate degree of malignancy and NSE in patients with small intestine lesions (22). NSE concentrations were not associated with gender or age.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…On the other hand, in our study, the analysis of concentrations in patients with small intestine lesions did not show a correlation between the degree of malignancy and the values of the marker determined. The results of our study did not confirm literature reports in which the authors indicate statistical differences already between low and intermediate degree of malignancy and NSE in patients with small intestine lesions (22). NSE concentrations were not associated with gender or age.…”
Section: Discussioncontrasting
confidence: 99%
“…This group of patients was characterised by significantly higher concentrations of the marker in relation to patients without liver metastases. The results of our study confirmed previous reports on the influence of liver lesions on NSE concentrations ( 21 , 22 ). These results are difficult to relate to the study reporting no effect of the presence of liver metastases on NSE levels because the authors do not specify the site of metastasis and the group of patients without metastases included only three patients ( 16 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…NSE is a glycolytic enzyme present in neurons and neuroendocrine cells in the central and peripheral nervous system. Elevated concentrations of NSE in body fluids can be found not only in septic shock and post-traumatic states, but also in conditions associated with cell proliferation, such as neoplasms [ 66 , 67 ]. The latter property was hoped to be useful in detecting NETs, however, research shows that NSE is elevated in just 19% of G1NET and 54% of G2NET cases.…”
Section: Discussionmentioning
confidence: 99%